DA7R: A 7-Letter Zip Code to Target PDAC - Sofia Parrasia; Andrea Rossa; Nicola Roncaglia; Andrea Mattarei; Claudia Honisch; Ildikò Szabò; Paolo Ruzza; Lucia Biasutto (Pharmaceutics, 2023)
Pancreatic ductal adenocarcinoma (PDAC) is the most common type of pancreatic cancer, and is among the most aggressive and still incurable cancers. Innovative and successful therapeutic strategies are extremely needed. Peptides represent a versatile and promising tool to achieve tumor targeting, thanks to their ability to recognize specific target proteins (over)expressed on the surface of cancer cells. A7R is one such peptide, binding neuropilin-1 (NRP-1) and VEGFR2. Since PDAC expresses these receptors, the aim of this study was to test if A7R-drug conjugates could represent a PDAC-targeting strategy. PAPTP, a promising mitochondria-targeted anticancer compound, was selected as the cargo for this proof-of-concept study. Derivatives were designed as prodrugs, using a bioreversible linker to connect PAPTP to the peptide. Both the retro-inverso (DA7R) and the head-to-tail cyclic (cA7R) protease-resistant analogs of A7R were tested, and a tetraethylene glycol chain was introduced to improve solubility. Uptake of a fluorescent DA7R conjugate, as well as of the PAPTP-DA7R derivative into PDAC cell lines was found to be related to the expression levels of NRP-1 and VEGFR2. Conjugation of DA7R to therapeutically active compounds or nanovehicles might allow PDAC-targeted drug delivery, improving the efficacy of the therapy and reducing off-target effects.